Biological Aspect of the Grey-eel catfish in Kuala Langsa Estuaries, Aceh - Teuku Fadlon Haser; Muh Saleh Nurdin; Fauziah Azmi; Muhammad Fauzan Isma; Suri Purnama Febri; Eddy Supriyono; Siska Mellisa (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2022)
The grey-eel catfish is a highly valued fish species in some parts of Indonesia. The fish is common in brackish water of estuaries, marine and freshwater habitat. They are not are not usually catched in commercial scale because of the limited population in its habitat. Although the status is not evaluated, the fish is predicted facing extinction in several countries. We conducted a study to examine the biological information and reproductive biology of the fish in Kota Langsa to gather information that can be utilize to evaluate reproductive status of the fish in several habitats. Parameters tested in the study includes sex ratio, length-weight relationships, candition factor, size at first maturity fecundity and reproductive potential of the fish. Research results provide information that the fish follows negative allometric model with constant condition factor throughout the study. The catches were relatively young fish which have not reached maturity stage. Fishes in the class sized at 510-550 mm provide the largest contribution to total eggs production. To ensure sustainability of the fish it is advised that the fish must catched at size larger than 550 mm.